Asma Jahangir: A Beacon of Human Rights in Pakistan and Beyond - Kamran; Saira Bano; Ahsan Ali (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The services rendered by the late Asma Jahangir, an advocate of the Supreme Court and a symbol of Human Rights, have been among the most outstanding contributions to humanity in Pakistan and abroad. As a human rights activist, she stood steadfast against all forms of aggression and raised her voice against the exploitation of the rights of women and minorities. She served as the founding Chairperson of the Human Rights Commission of Pakistan, an independent group, and remained a trustee of the international crisis group. This paper highlights Asma Jahangir’s services in various aspects of life, including Human Rights, Children’s Rights, and the rights of minorities. The methodology is based on qualitative research techniques, and secondary sources have been utilized for data collection and content analysis. This study holds significance as it is the first of its kind in the field of human rights and is expected to make a substantial contribution to existing literature.